Evaluation of Malaysia’s food balance of trade plan : achievement rates. - Mohamed Arshad, Fatimah; Mohd. Noh, Kusairi (World Business Institute, 2010)
Malaysia has always been a net food importer in the last four decades. In 2007, the deficit in the food trade stood at RM9.7 billion (or USD2.9 billion). In 2002, Malaysia implemented a policy towards achieving a surplus balance of trade in food of RM1.2 billion (or USD352 billion) by 2010. This paper evaluates the policy in terms of the achievement rates of the plan. The analysis suggests that the actual trade data shows the intended targets are likely not to be met; in fact the deficit is expected to grow bigger with time. While the objective was commendable, the targets, rationales and strategies for such a plan require a serious rethinking.